2017
DOI: 10.1155/2017/9474532
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Epithelial-Mesenchymal Transition Phenotypes of Circulating Tumor Cells and the Clinicopathological Features of Patients with Colorectal Cancer

Abstract: In this study, we identified CTCs using the previously reported CanPatrol CTC enrichment technique from peripheral blood samples of 126 patients with colorectal cancer (CRC) and found that CTCs could be classified into three subpopulations based on expression of epithelial cell adhesion molecule (EpCAM) (E-CTCs), the mesenchymal cell marker vimentin (M-CTCs), or both EpCAM and vimentin (biphenotypic E/M-CTCs). Circulating tumor microemboli (CTMs) were also identified in peripheral blood samples. Meanwhile, E-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…A recent study of CTCs isolated from breast cancer patients and mouse models, reported that the binding sites for CSC transcription factors such as OCT4, SOX2, or NANOG, are hypomethylated in CTC clusters compared with isolated CTCs [49]. Other data collected from human samples also emphasize the presence of hybrid E/M phenotypes in heterogeneous CTC clusters, particularly in lung cancers [51,52,109,190]. Very elegantly, a study by Yu and coworkers identified cells expressing both epithelial (such as EpCAM or cytokeratins) and mesenchymal markers (including fibronectin, N-cadherin or PAI-1) in isolated CTCs but also in CTC clusters from breast cancer patients [179].…”
Section: Traveling In Clustersmentioning
confidence: 98%
“…A recent study of CTCs isolated from breast cancer patients and mouse models, reported that the binding sites for CSC transcription factors such as OCT4, SOX2, or NANOG, are hypomethylated in CTC clusters compared with isolated CTCs [49]. Other data collected from human samples also emphasize the presence of hybrid E/M phenotypes in heterogeneous CTC clusters, particularly in lung cancers [51,52,109,190]. Very elegantly, a study by Yu and coworkers identified cells expressing both epithelial (such as EpCAM or cytokeratins) and mesenchymal markers (including fibronectin, N-cadherin or PAI-1) in isolated CTCs but also in CTC clusters from breast cancer patients [179].…”
Section: Traveling In Clustersmentioning
confidence: 98%
“…3 While there is obvious heterogeneity among CTCs, CTCs can be defined as epithelial type (eCTC), mesenchymal type (mCTC), biophenotypic type (bCTC), and CTCs mass (CTM) according to different expression patterns of epithelial and mesenchymal markers of CTCs. [5][6][7] Wu et al 8 reported that changes in gene expression in CTCs can affect the prognosis of CRC, such as the expression of mesenchymal markers. [5][6][7] Wu et al 8 reported that changes in gene expression in CTCs can affect the prognosis of CRC, such as the expression of mesenchymal markers.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (11) demonstrated that postoperative CTC positivity was independently associated with a shorter 3-year recurrence-free survival rate compared with preoperative CTC positivity. In a study by Wu et al (12), the detection rates of epithelial CTCs, mesenchymal CTCs (M-CTC)s, epithelial/mesenchymal CTCs and circulating tumor microembolis (CTMs) in 126 patients with CRC were 76.98, 42.06, 56.35 and 36.51%, respectively. Additionally, the metastases of tumors in patients with CRC who had CTMs and M-CTCs had a higher risk of tumor metastasis compared with patients in the other CTC subgroups (12).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Wu et al (12), the detection rates of epithelial CTCs, mesenchymal CTCs (M-CTC)s, epithelial/mesenchymal CTCs and circulating tumor microembolis (CTMs) in 126 patients with CRC were 76.98, 42.06, 56.35 and 36.51%, respectively. Additionally, the metastases of tumors in patients with CRC who had CTMs and M-CTCs had a higher risk of tumor metastasis compared with patients in the other CTC subgroups (12). A study also revealed that the expression of leucine-rich repeat-containing G protein-coupled receptor 5 in CTCs was significantly associated with the incidence of CRC metastasis (13).…”
Section: Introductionmentioning
confidence: 99%